Gender and the development of handicraft production in rural Yucatán/Mexico - Eva Youkhana (University of Bonn, Center for Development Research (ZEF), 2010)
Using the example of a development project to increase tourism and improve artisan production in a Maya community, the study explores traditional gender roles and transformation processes in a village where handicraft production became the most dynamic rural economy. The study focuses on the relationship between project executors and peasant artisan women and describes processes of inclusion and exclusion that arose during project implementation. By describing the interface between the care and commodity economies, it is shown how the gendered division of labor was partly overcome, and how new dependencies arose simultaneously. Furthermore, it is documented in which way development projects are accompanied by resources appropriation of powerful interest groups. This paper also addresses the origins of the division of labor and development of handicraft production in Yucatán and describes in how the national tourism industry is taking advantage of segments of the population to construct Mexican identity. The paper argues that the 'artinisation' of the rural indigenous population is a poor substitute for their integration into the national economy, within which women's perspective turns out to be exploited in many ways.
Keywords: 330; Mexico; gender; tourism; peasant artisans; participatory development